The domino gene of Drosophila encodes novel members of the SWI2/SNF2 family of DNA-dependent ATPases, which contribute to the silencing of homeotic genes. - Ruhf, M.L.; Braun, A.; Papoulas, O.; Tamkun, J.W.; Randsholt, N.; Meister, M. (Development, 2001)
The Drosophila domino gene has been isolated in a screen for mutations that cause hematopoietic disorders. Generation and analysis of loss-of-function domino alleles show that the phenotypes are typical for proliferation gene mutations. Clonal analysis demonstrates that domino is necessary for cell viability and proliferation, as well as for oogenesis. domino encodes two protein isoforms of 3202 and 2498 amino acids, which contain a common N-terminal region but divergent C termini. The common region includes a 500 amino acid DNA-dependent ATPase domain of the SWI2/SNF2 family of proteins, which function via interaction with chromatin. We show that, although domino alleles do not exhibit homeotic phenotypes by themselves, domino mutations enhance Polycomb group mutations and counteract Trithorax group effects. The Domino proteins are present in large complexes in embryo extracts, and one isoform binds to a number of discrete sites on larval polytene chromosomes. Altogether, the data lead us to propose that domino acts as a repressor by interfering with chromatin structure. This activity is likely to be performed as a subunit of a chromatin-remodeling complex.